Molecular Epidemiology of Clinical and Colonizing Methicillin-Resistant Staphylococcus Isolates in Companion Animals - Rynhoud, Hester; Forde, Brian M.; Beatson, Scott A.; Abraham, Sam; Meler, Erika; Soares Magalhães, Ricardo J.; Gibson, Justine S. (Frontiers in Veterinary Science, 2021)
In this study we aimed to investigate the molecular epidemiology of methicillin resistant Staphylococcus aureus (MRSA) and methicillin resistant Staphylococcus pseudintermedius (MRSP) clinical and colonising isolates of dogs and cats to profile contributing factors associated with their isolation. Nasal and rectal samples were collected from dogs and cats between 2015 and 2017 to identify colonising isolates. Clinical isolates collected between 2003 and 2016 were retrieved from a Queensland university veterinary diagnostic laboratory. All isolates were identified using standard microbiological and molecular methods and were characterised by whole genome sequencing. Phylogenetic relationships and differences in epidemiological factors were investigated. Seventy-two MRSP isolates out of 1,460 colonising samples and 9 MRSP clinical isolates were identified. No MRSA was isolated. ST496 and ST749 were the most commonly isolated sequence types with different SCCmec types. ST496 clones spread both along the coast and more inland where ST749 was more centred on Brisbane city. The resistance and virulence factors differed significantly between the two sequence types. ST496 colonising and clinical isolates were similarly multidrug resistant. The virulence genes of ST749 colonising and clinical isolates were similar as both contained the gene nanB for sialidase. There were no differences in the individual and clinical factors between predominant sequence types. High levels of antimicrobial resistance occurred in the majority of isolates which is of potential concern to human and veterinary health. The phylogenetic clustering of isolates from this study and others previously identified in countries, particularly New Zealand, with which Australia has high volume of pets movements could suggest the importation of clones which needs further investigation.